MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: R

There are no items in this cart.
Continue Shopping
Menu
Get instant 20% OFF on Online Material.
coupon code: MOB20 | View Course list

  • Complete JEE Main/Advanced Course and Test Series
  • OFFERED PRICE: R 15,000
  • View Details
Get extra R 4,500 off
USE CODE: Venkat30

Solved Examples on Determinants

Illustration 1: Let M and N be two 3 x 3 non-singular skew-symmetric matrices such that MN = NM. If PT denotes the transpose of P then M2N2 (MTN)-1(MN-1)T is equal to (2011)

1. M2                                                                2. –N2

3. –M2                                                              4. MN

Solution: It is given that M and N are two 3 x 3 non-singular skew-symmetric matrices, so MT = -M and NT = -N

Also, MN = NM    …….. (1)

Now, we need to compute M2N2 (MTN)-1 (MN-1)T

Using the property of inverse, we have

M2N2 (N)-1 (MT)-1 (N-1)T (M)T

⇒ M2N (NN-1) (-M)-1 (NT)-1 (-M)     (using the results MT = -M and NT = -N)

= M2NI (-M)-1 (-N)-1 (-M)

= -M2NM-1N-1M

= -M (MN) M-1N-1M

= -M (NM) M-1N-1M

= -MN (MM-1) N-1M

= -M (NN-1) M

= -M2

 

Illustration 2: Let μ and α be real. Find the set of all values of μ for which the system of linear equations

μx + (sin α)y + (cos α) z = 0

x + (cos α) y + (sin α) z = 0

and -x + (sin α) y - (cos α) z = 0

has a non-trivial solution. For μ =1, find all values of α. (1993)

Solution: Given system is μx + (sin α)y + (cos α) z = 0

x + (cos α) y + (sin α) z = 0

also, -x + (sin α)y - (cos α) z = 0 has non-trivial solution.

Therefore, determinant i.e. Δ = 0


This gives μ (-cos2α - sin2α) – sin α (-cos α + sin α) + cos α (cos α + sin α) = 0.

⇒ -μ + sin α cos α + sin α cos α - sin2α + cos2α = 0.

⇒ μ = cos 2α + sin 2α (since – √a2+b2 ≤ a sin θ + b cos θ ≤ √a2+b2)

Hence, we get –√2 ≤ μ ≤ √2    …….. (1)

Again, when μ = 1, cos 2α + sin 2α = 1

⇒ 1/√2 cos 2α + 1/√2 sin 2α = 1/√2 

⇒ cos (2α – π/4) = cos (π/4)

Therefore, 2α – π/4 = 2nπ ± π/4

⇒ 2α = 2nπ - π/4 + π/4

⇒ 2α = 2nπ + π/4 + π/4

Hence, α = nπ or α = nπ + π/4

 

Illustration 3: Suppose f(x) is a function satisfying the following conditions:

(a) f(0) = 2, f(1) = 1

(b) f has a minimum value at x =5/2 and

(c)...

  • Complete AIPMT/AIIMS Course and Test Series
  • OFFERED PRICE: R 15,000
  • View Details
Get extra R 4,500 off
USE CODE: Venkat30